ANALISIS KINERJA BELANJA DAERAH KABUPATEN KARAWANG DAN TANTANGANNYA DALAM MENDUKUNG PENCAPAIAN PERTUMBUHAN BERKUALITAS - Salhefni Salhefni (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
The economic development of Karawang Regency has reached a good level, but in fact it still faces some quite concerning problems, including poverty and income inequality. This study aims to analyze the performance of regional spending in Karawang Regency and the relationship of several macroeconomic variables with the three fiscal policy functions. In addition, analyzing challenges in improving APBD performance and alternative solutions to address these challenges. The method of analysis uses descriptive analysis, by applying the data collection method based on a desk study. The results showed that the performance of the Karawang regency budget in terms of the quality of regional spending showed a low performance. Based on the allocation and distribution functions, the Karawang Regency APBD is still not optimal in providing stimulus to the regional economy and resolving income and development inequalities. There are several challenges in improving the performance of the Karawang Regency APBD, including delays in budget disbursement, accumulation of transactions at the end of the year, understanding in budget preparation and subjectivity in budget allocation. To answer problems related to budget disbursement governance, a credible budget system is required.